Head-up Tilt Test with Isoproterenol Provocation in Syncope of Unknown Origin - Ryu, Moon Hee (Korean J Intern Med, 1996)
OBJECTIVES: Head-up tilt test (HUT) has been reported to be useful in the evaluation of syncope of unknown origin (SUO). However, the sensitivity of HUT with no pharmacologic provocation was relatively low and variable, ranging 32–70%. Therefore, several protocols of HUT with different degrees and durations of the tilt and modes of provocation were proposed. The purpose of this study was to determine the value of the multi-stage head-up tilt test with isoproterenol provocation (HUT-isp) in the evaluation of SUO and drug efficacy. METHODS: Sixty-seven patients presenting with SUO and 30 control subjects with no history of syncope underwent the HUT-isp. Blood pressure (BP) was measured every 2 min and whenever the patient complained of any symptom, and cardiac rhythm was continuously monitored. The HUT-isp consisted of 3 stages: first for 20 min with no provocation, second and third stages with infusion of isoproterenol for 10 min each at a rate of 2 μg/min and 5 μg/min, respectively. A positive HUT-isp was defined when syncope or presyncope was reproduced, accompanied by hypotension (< 80 mmHg) or bradycardia (< 40/min) or both, and positive responses were classified into vasodepressive, cardioinhibitory and mixed type. RESULTS: The HUT-isp was positive in 56 (83.6%) of 67 patients with SUO and 10 (33.3%) of 30 control subjects. The type of positive responses was vasodepressive in 41 (73.2%), cardioinhibitory in 4 (7.1%) and mixed in 11 (19.6%). The sensitivity of the HUT-isp in diagnosing vasovagal syncope was 83.6%, specificity 66.7% and positive predictive value 84.8%. Positive responses were developed most frequently in the 3rd stage: 76.8% in patients, 70% in controls. The effect of 3 drugs (carteolol, aminophylline and disopyramide) was evaluated in 27 patients with a repeat HUT-isp. Carteolol was effective in 12 (85.7%) of 14 patients, disopyramide in 7 (58.3%) of 12 and aminophylline in 1 (14.3%) of 7. During the follow-up period of 175±212 days (26–623 days), none of the 20 patients with a negative repeat HUT-isp developed a recurrent syncope. CONCLUSION: The HUT-isp is thought safe and useful to evaluate syncope of unknown origin and to guide effective drug therapy.